A single‐station empirical model for TEC over the Antarctic Peninsula using GPS‐TEC data. Issue 2 (10th February 2017) - Feng, Jiandi; Wang, Zhengtao; Jiang, Weiping; Zhao, Zhenzhen; Zhang, Bingbing
Abstract: Compared with regional or global total electron content (TEC) empirical models, single‐station TEC empirical models may exhibit higher accuracy in describing TEC spatial and temporal variations for a single station. In this paper, a new single‐station empirical total electron content (TEC) model, called SSM‐month, for the O'Higgins Station in the Antarctic Peninsula is proposed by using Global Positioning System (GPS)‐TEC data from 01 January 2004 to 30 June 2015. The diurnal variation of TEC in the O'Higgins Station may have changing features in different months, sometimes even in opposite forms, because of ionospheric phenomena, such as the Mid‐latitude Summer Nighttime Anomaly (MSNA). To avoid the influence of different diurnal variations, the concept of monthly modeling is proposed in this study. The SSM‐month model, which is established by month (including 12 submodels that correspond to the 12 months), can effectively describe the diurnal variation of TEC in different months. Each submodel of the SSM‐month model exhibits good agreement with GPS‐TEC input data. Overall, the SSM‐month model fits the input data with a bias of 0.03 TECU (total electron content unit, 1 TECU = 10 16  el m −2 ) and a standard deviation of 2.78 TECU. This model, which benefits from the modeling method, can effectively describe the MSNA phenomenon without implementing any modeling correction. TEC data derived from Center for Orbit Determination in Europe global ionosphere maps (CODE GIMs), International Reference Ionosphere 2012 (IRI2012), and NeQuick are compared with the SSM‐month model in the years of 2001 and 2015–2016. Result shows that the SSM‐month model exhibits good consistency with CODE GIMs, which is better than that of IRI2012 and NeQuick, in the O'Higgins Station on the test days. Key Points: A new single‐station empirical total electron content (TEC) model, called SSM‐month, for the O'Higgins Station in the Antarctic Peninsula The SSM‐month model is established by month, including 12 submodels that correspond to the 12 months SSM‐month model exhibits good consistency with CODE/TEC, which is better than that of IRI2012, in the O'Higgins Station on the test days